2015
DOI: 10.1007/s12010-015-1858-x
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimization for Decaffeination and Theophylline Production by Fusarium solani

Abstract: Coffee processing industries generate caffeine-containing waste that needs to be treated and decaffeinated before being disposed. Five fungal isolates obtained on caffeine-containing mineral media were tested for their ability to utilize caffeine at high concentrations. An isolate identified as Fusarium solani could utilize caffeine as a sole source of carbon and nitrogen up to 5 g/l and could degrade it to an extent of 30-53 % in 120 h. Sucrose that was added as an auxiliary substrate (5 g/l) enhanced the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Also the antioxidant capacity of caffeine and TPh, mainly as HO · scavenger, has been discussed more recently. [5][6][7] On the other hand, the wide pharmaceutical employ of TPh in human and in veterinary medicine, [8] added to the important industrial processes concerning coffee, cocoa and tea, led to its ubiquitous detection in the aquatic environment, as recently reported. [9] Furthermore, several studies reported an acute toxicity to mammals and human, especially when mixed with other pharmaceuticals, [10][11] so that TPh can be considered among the emerging pharmaceutical pollutants of aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Also the antioxidant capacity of caffeine and TPh, mainly as HO · scavenger, has been discussed more recently. [5][6][7] On the other hand, the wide pharmaceutical employ of TPh in human and in veterinary medicine, [8] added to the important industrial processes concerning coffee, cocoa and tea, led to its ubiquitous detection in the aquatic environment, as recently reported. [9] Furthermore, several studies reported an acute toxicity to mammals and human, especially when mixed with other pharmaceuticals, [10][11] so that TPh can be considered among the emerging pharmaceutical pollutants of aquatic environment.…”
Section: Introductionmentioning
confidence: 99%
“…F. solani capable of degrading caffeine was isolated from caffeine-contaminated soil. Response surface optimization for decaffeination and theophylline production by the fungus showed that a pH of 5.8, temperature of 24°C, and inoculum size of 4.8 9 10 5 spores/mL have resulted in a complete biodecaffeination of caffeine as well as the production of theophylline with a yield of 33% (Nanjundaiah et al 2016). Compared with the previous reports, this work shows that resting cells of Aureobasidium sp.…”
Section: Resultsmentioning
confidence: 55%
“…Until now, several pure fungal isolates belonging to the genus Penicillium, Aspergillus, Stemphylium, Rhizopus, and Fusarium capable of degrading caffeine have been identified. However, only Penicillium citrinum and Fusarium solani produced substantial amounts of theophylline from caffeine biotransformation, as these fungi can produce theophylline in concentrations of 0.78 g/L (molar yield 85%) and 0.33 g/L (molar yield 35.5%), respectively (Patra 2007;Nanjundaiah et al 2016). In view of this background, the study focuses on the isolation and identification of caffeine-degrading fungi to explore their ability in the biotransformation of caffeine to theophylline.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is slowly degraded by consecutive removal of the three methyl groups, resulting in the formation of xanthine in almost all caffeine-forming plant species, with theophylline being a mid-product of the process [55]. Caffeine [58], theobromine [59] and theophylline [60] may also be obtained by chemical synthesis.…”
Section: Natural Sources Of Methylxanthines and Biosynthesismentioning
confidence: 99%